7. COMPARISON OF RAPID CENTRIFUGATION WITH ROUTINE CENTRIFUGATION FOR SOME COAGULATION TESTING (PT, APTT, FIBRINOGEN) AT DEPARTMENT OF HEMATOLOGY IN VIETDUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: Comparison of rapid centrifugation (2300g in 5 minutes) with routine centrifugation (1500g  in 15 minutes) for some coagulation testing (PT, APTT and fibrinogen) at Department of Hematology in Vietduc University Hospital.Methods: Experimental study on 45 pairs of patient samples according to the Clinical and Laboratory Standards Institute (CLSI) guideline for Method Comparison and Bias Estimation Using Patient Samples (EP09c).Results: Platelet count after rapid centrifugation was 3.53 ± 1.50 G/l, similar to routine centrifugation (3.45 ± 1.58 G/l) with no statistically significant difference (p > 0.05). The results of Passing-Bablok linear regression analysis and Bland-Altman difference plot estimation showed that the difference in PT-INR and APTT-r and fibrinigen between the two centrifugation methods was within acceptable limits.Conclusions: The present study showed no no statistically significant difference when comparable results between rapid (2300g × 5 minutes) and routine (1500g × 15 minutes) centrifugation techniques for some coagulation screening test (PT and APTT and fibrinogen). Rapid centrifugation can be used in emergency coagulation screening tests, especially in red code situations.
Keywords: Method comparison; CLSI-EP09c; rapid centrifugation